Encyclopaedia of educational psychology # Encyclopaedia of educational psychology, Vol.2 Teachers, teaching and educational psychology Vol.3 - Nayak, Ramesh K.; Chawla, Ganesh Kumar (New Delhi Arpan Publishing, 2013)
Educational technology in teacher education